A Comparative Study Between Active Chin Tuck Exercise Versus Versatile Muscle Therapy With Ultrasound Therapy In Subjects Who Have Mechanical Neck Pain (International Journal of Food and Nutritional Sciences, 2022)
BACKGROUND AND PURPOSE: Thisresearch has beenconducted for comparing the difference between the impacts ofactive chin tuck exercises versus versatile muscle therapy with ultrasound therapy insubjects with neck pain. DESIGN:Quasi-experimentalstudydesign METHODS: 30 computer experts between the ages of 20 and 40 who met the requirements were chosen at random and divided into two groups, each with 15 subjects. Group A was assigned to Active chin tuckexercise with Ultrasound therapy and Group B to Versatile muscle therapy (using a sub-occipital release tool)with Ultrasoundtherapy. The research has been completed in a period of 3 weeks. Before and after the intervention, neck functionality and range of motion were assessed using the Copenhagen Neck Functional Disability Scale and the Goniometer, respectively, and the results were evaluated. Result: The study showed an improvementinNeck function andan increase in ROM among desktop professionals treatedwithActivechin tuck exercises with Ultrasound therapy & also in groups treated with Versatilemuscletherapywith Ultrasound therapyfor patients with cervical pain.It is concluded thatActive chin tuck exercise withUltrasound therapyrevealed an improvementinneckfunction and Range of Motion.